Blocking development of liver fibrosis augments hepatic progenitor cell‐derived liver regeneration in a mouse chronic liver injury model. Issue 9 (29th May 2019) - Kitade, Mitsuteru; Kaji, Kosuke; Nishimura, Norihisa; Seki, Kenichiro; Nakanishi, Keisuke; Tsuji, Yuki; Sato, Shinya; Saikawa, Soichiro; Takaya, Hiroaki; Kawaratani, Hideto; Namisaki, Tadashi; Moriya, Kei; et al.
Abstract : Aim: The roles of hepatic progenitor cells (HPCs) in regeneration of a diseased liver are unclear. Hepatic stellate cells (HSCs) contribute to liver fibrosis but are also a component of the HPC niche. Hepatic progenitor cells expand along with HSC activation and liver fibrosis. However, little is known about the interplay of liver fibrosis and HPC‐mediated liver regeneration. This study aimed to investigate HSCs and HPCs in liver regeneration. Methods: Liver injury in mice was induced with 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine, and HPC expansion and fibrosis were assessed. An angiotensin II type 1 receptor blocker (ARB) was administered to assess its effect on fibrosis and regeneration. Results: Treatment with ARB attenuated fibrosis and expansion of α‐smooth muscle actin‐positive activated HSCs as indicated by increased liver weight and Ki‐67‐positive hepatocytes. Immunohistochemical staining suggested that HPC differentiation was shifted toward hepatocytes (HCs) when ARB treatment decreased HPC encapsulation by HSCs and extracellular matrix. Conditioned medium produced by culturing the human HSC LX‐2 line strongly augmented differentiation to biliary epithelial cells (BECs) but inhibited that to HCs. Activated HSCs expressed Jagged1, a NOTCH ligand, which plays a central role in differentiation of HPCs toward BECs. Conclusions: Hepatic stellate cells, the HPC niche cells, control differentiation of HPCs, directing them toward BECs rather than HCs in a diseased liver model. Antifibrosis treatment with an ARB preferentially redirects HPC differentiation toward HCs by blocking the NOTCH pathway in the HPC niche, resulting in more efficient HPC‐mediated liver regeneration.